1981
DOI: 10.1007/bf01542176
|View full text |Cite
|
Sign up to set email alerts
|

A study of pre- and postsurgical transsexuals: MMPI characteristics

Abstract: This study examines assessment issues concerning transsexualism through the use of the Minnesota Multiphasic Personality Inventory (MMPI). The MMPI was administered to 20 transsexuals matched within sex on age and education: five presurgical male-to-females, five postsurgical male-to-females, five presurgical female-to-males, and five postsurgical female-to-males. Mean T scores for each of these four subsamples were examined in comparison to normative groups. Comparisons among the four subsamples showed signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…Consistent with previous studies, the scales on which the highest proportions of individuals scored in the clinical range were Masculinity/Femininity and Psychopathic Deviate 3 5 28 31 36 37 . As expected 3 7 10 37 , the Masculinity/Femininity scale is where both biological men and women most frequently showed profiles in the clinical range 5 .…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with previous studies, the scales on which the highest proportions of individuals scored in the clinical range were Masculinity/Femininity and Psychopathic Deviate 3 5 28 31 36 37 . As expected 3 7 10 37 , the Masculinity/Femininity scale is where both biological men and women most frequently showed profiles in the clinical range 5 .…”
Section: Discussionsupporting
confidence: 89%
“…Results have been inconsistent: Cole et al (1997) and Hunt et al (1981) found both MtF and FtM transsexuals to be, for the most part, "notably free of psychopathology" (Cole et al, 1997, p. 13) based on MMPI results; Miach et al (2000), Michel et al (2002), and Tsushima and Wedding (1979) reached similar conclusions in studies of MtF transsexuals. However, Beatrice (1985) and Langevin et al (1977) reported significant psychopathology in some MtF transsexuals based on MMPI studies, as did Fleming et al (1981) in both MtF and FtM transsexuals; the most common findings included antisocial tendencies, thought disorder, or hypomania. MMPI data suggest, however, that transsexuals tend to experience less psychopathology than transgender persons who meet criteria for the DSM-III-R diagnosis of Gender Identity Disorder of Adolescence and Adulthood, Nontranssexual Type (GIDAANT) (Miach et al, 2000;Michel et al, 2002).…”
Section: Other Mental Health Concerns In Transgender Personsmentioning
confidence: 91%
“…MMPI data suggest, however, that transsexuals tend to experience less psychopathology than transgender persons who meet criteria for the DSM-III-R diagnosis of Gender Identity Disorder of Adolescence and Adulthood, Nontranssexual Type (GIDAANT) (Miach et al, 2000;Michel et al, 2002). MMPI data also suggest that mental health typically improves following gender transition in MtF transsexuals (Langevin et al, 1977) and following SRS in both MtF and FtM transsexuals (Fleming et al, 1981; but see Beatrice, 1985). Beatrice (1985) found no evidence of psychopathology in a small group of male cross-dressers based on MMPI results.…”
Section: Other Mental Health Concerns In Transgender Personsmentioning
confidence: 98%
“…The MMPI, however, has shown the most promise as a clinical instrument for identifying and predicting gender dysphoria. The published studies have used the MMPI to: (a)determine psychiatric diagnosis (Finney, Brandsma, Tondow, & LeMaestre, 1975); (b)describe a mean MMPI patient profile (Lothstein, 1980;Lothstein, Althof, Jones, & Shen, Note 3; Paitich, Note 4); (c)contrast gender dysphoria patients with other patient groups, using mean profiles (Lothstein et al, Note 3); and (d)contrast the patient's pre-and posttreatment scores on a single measure (Fleming, Cohen, Salt, Jones, & Jenkins, 1981;Hill, 1980). The results of these studies respectively indicate: (a) a preponderance of hysterical diagnoses; (b)elevations on Scale 5, with the most prevalent two-point clinical codes being 5-4/4-5 and 5-818-5; (c)the mean profiles of gender patients suggest less psychopathology than those of outpatients in control groups; (d) treatment significantly lowers patients' scores on MMPI clinical scales.…”
Section: Psychological Testingmentioning
confidence: 99%